(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: There is a relatively poor understanding of the pathogenesis of pelvic endometriomas, as is the whole subject of endometriosis. The pathophysiological basis of endometriosis remains enigmatic, especially for endometriomas. Diagnostic acumen has remained low; therefore, a standardized objective treatment approach is elusive. Objective: To elucidate possible pathogenetic processes and collate them with clinical and treatment outcomes. Results: This is a relatively neglected pathologic process that affects the ovary. It is a composite component of pelvic peritoneal endometriosis with a heavier predilection toward the ovary as the target organ. Infertility is a very common outcome because of reduced ovarian reserve and the inflammatory processes that often accompany the pelvic peritoneal component. Endometriomas are very common, as reflected by the finding that 17-44% of patients with ovarian cysts have endometriomas, and endometriomas constitute 35% of benign ovarian cysts. Conclusion: The propensity of the condition, coupled with the pathophysiological impact, dictates a need for a better understanding of pathogenesis and conservative treatment that targets fertility preservation.